Akhlak Dan Etika Kepemimpinan Dalam Perubahan Lembaga Dakwah - Kendy, Muhammad; Castrawijaya, Cecep (Program Studi Manajemen Dakwah, Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2025)
Islamic propagation institutions are crucial for spreading religious teachings and strengthening religious values ​​within society. In line with social dynamics, technological developments, and the challenges of the times, Islamic propagation institutions are required to continuously adapt and change. In this process, the role of leaders is vital. Leaders not only act as organizational directors but also as agents of change capable of encouraging innovation and improving the quality of Islamic propagation. Effective leadership involves the ability to structure the organization, distribute tasks and authority, formulate policies, and motivate members to achieve common goals. Leaders are also responsible for evaluating Islamic propagation results, identifying deviations, and formulating solutions to improve the effectiveness of Islamic propagation programs. Thus, the success of Islamic propagation institutions is largely determined by the quality of leadership in responding to change and strategically managing the organization.